Silencing of OsCV (chloroplast vesiculation) maintained photorespiration and N assimilation in rice plants grown under elevated CO2. (3rd February 2020) - Umnajkitikorn, Kamolchanok; Sade, Nir; Rubio Wilhelmi, Maria del Mar; Gilbert, Matthew E.; Blumwald, Eduardo
Abstract: High CO2 concentrations stimulate net photosynthesis by increasing CO2 substrate availability for Rubisco, simultaneously suppressing photorespiration. Previously, we reported that silencing the chloroplast vesiculation ( cv ) gene in rice increased source fitness, through the maintenance of chloroplast stability and the expression of photorespiration‐associated genes. Because high atmospheric CO2 conditions diminished photorespiration, we tested whether CV silencing might be a viable strategy to improve the effects of high CO2 on grain yield and N assimilation in rice. Under elevated CO2, OsCV expression was induced, and OsCV was targeted to peroxisomes where it facilitated the removal of OsPEX11‐1 from the peroxisome and delivered it to the vacuole for degradation. This process correlated well with the reduction in the number of peroxisomes, the decreased catalase activity and the increased H2 O2 content in wild‐type plants under elevated CO2 . At elevated CO2, CV ‐silenced rice plants maintained peroxisome proliferation and photorespiration and displayed higher N assimilation than wild‐type plants. This was supported by higher activity of enzymes involved in NO3 − and NH4 + assimilation and higher total and seed protein contents. Co‐immunoprecipitation of OsCV ‐interacting proteins suggested that, similar to its role in chloroplast protein turnover, OsCV acted as a scaffold, binding peroxisomal proteins. Abstract : This work, follows our initial characterization of chloroplast vesiculation ( cv ), a protein associated with stress‐induced chloroplast degradation [Plant Cell 26:4875–4, 888 (2014); J. Exp. Bot 69:867–878 (2018)]. Here, we tested whether CV silencing in rice affected yields and N assimilation of rice grown under high CO2 . We show that under high CO2, OsCV was targeted to the peroxisome and interacted with OsPEX11‐1 and delivered OsPEX11‐1 to the vacuole for degradation. Under high CO2, CV ‐silenced rice plants maintained peroxisome proliferation and displayed photorespiration and higher N assimilation than WT plants.